Determination of 107 Pesticide Residues in Citrus Fruits by Gas Chromatography/ Mass Spectrometry - Taga, O.; Bilgin, B. (Asian Journal of Chemistry, 2010)
This study was carried out to investigate the organochlorine (OC), organophosphorus (OP) and organochlorine and organophosphorus (OC and OP) pesticide residues in citrus fruit samples (mandarin, orange and lemon) collected from the Aegean and Mediterranean regions of Turkey. Sample preparation and extraction were performed using Luke extraction method. The concentrations of pesticides were determined by gas chromatography with selective detectors: electron capture detector, nitrogen phosphorus detector and mass selective detector and confirmed with mass-spectrometry. At least one type of pesticide residue was found in 105 samples out of 210 (50 %). In 5 samples (2.4 %), the residue levels were found above the maximum residue levels of Turkish food codex and European union standards.